Changes in Open Defecation in Rural North India: 2014-2018 - Aashish Gupta; Nazar Khalid; Devashish Desphande; Payal Hathi; Avani Kapur; Nikhil Srivastav; Sangita Vyas; Dean Spears; Diane Coffey (Institute of Labor Economics (IZA), 2019)
Since October 2014, the Government of India has worked towards a goal of eliminating open defecation by 2019 through the Swachh Bharat Mission (SBM). In June 2014, we reported the results of a survey of rural sanitation behaviour in north India. Here, we report results from a late 2018 survey that revisited households from the 2014 survey in four states: Bihar, Madhya Pradesh, Rajasthan, and Uttar Pradesh. Although rural latrine ownership increased considerably over this period, open defecation remains very common in these four states. There is substantial heterogeneity across states in what the SBM did and how. Many survey respondents report that the SBM attempted to coerce latrine construction, including by withholding or threatening to withhold government benefits. ST and SC households were especially likely to face coercion. Variation in SBM coercion is correlated with variation in sanitation outcomes: in villages where more people report coercive SBM activities, more people also reported switching to latrine use. These outcomes suggest the need for transparent, fact-based public dialogue about the SBM: its costs and benefits, its accomplishments and means.
Keywords: O15; I15; 330; sanitation; open defecation; India; development; environmental health; behaviour; Swachh Bharat Mission